2021
DOI: 10.1016/j.celrep.2021.110116
|View full text |Cite|
|
Sign up to set email alerts
|

Purkinje cells translate subjective salience into readiness to act and choice performance

Abstract: Highlights d Cerebellar encoding of sensorimotor and cognitive modalities depends on context d Purkinje cell complex spike activity reflects perceived salience of sensory inputs d Timing of complex spikes shifts when a readiness to act is required d Simple spike modulation adheres to choice performance and motor activity

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 90 publications
1
16
0
Order By: Relevance
“…The input from the inferior olive to the cerebellum conveys information that guides learning ( 39, 40 ), but this same input also provides information about diverse sensory and motor events that are not errors ( 7, 10, 12 ). In our task, we observed that the olivary input to P-cells was modulated following the onset of visual targets, and before the onset of saccades towards those targets ( 20, 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The input from the inferior olive to the cerebellum conveys information that guides learning ( 39, 40 ), but this same input also provides information about diverse sensory and motor events that are not errors ( 7, 10, 12 ). In our task, we observed that the olivary input to P-cells was modulated following the onset of visual targets, and before the onset of saccades towards those targets ( 20, 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these rate changes are not specific to erroneous movements ( 6 ). Rather, the CS rates change in response to a variety of sensory events ( 712 ), and before a variety of movements ( 1317 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The circuit, which could account for the previously observed short-latency cerebello-amygdala responses 37 , could convey cerebellar information about prediction, salience and/or valence to BLA, shaped by the intrinsic, synaptic and integrative properties of the nodes. Indeed, the cerebellum is known to encode such information 8,[69][70][71][72][73] , which is also seen in BLA 35,[74][75][76][77][78][79] , and which is thought to be used by CM and PF during aversive conditioning, observational learning and reward-seeking behavior 30,46,[80][81][82][83] .…”
Section: Proposed Functions Of the Dcn-bla Circuitmentioning
confidence: 99%
“…( 6 ) have provided compelling evidence that dynamic patterning of CS synchrony may allow for different combinations of muscles to be used to facilitate the timing and sequence of movements. Indeed, synchronized patterns of CS activity may contribute not only to the initiation of relatively simple reflex movements ( 7 , 8 ) but also to more complex types of behaviors that require extensive training over time ( 9 12 ). Moreover, recent studies raise the possibility that CS signaling, and thereby CS synchrony, in particular microzones, might also be involved in reward signaling following acquisition of complex behaviors ( 9 , 13 , 14 ).…”
mentioning
confidence: 99%